'Behind-the-Border' Regulatory Policies and Trade Agreements - Bernard Hoekman (East Asian Economic Review (EAER), 2018)
A consequence of global trade liberalization is that domestic regulatory policies have become a focal point for efforts to reduce the costs of engaging in cross-border production and exchange. This article discusses the general challenges of reducing trade frictions created by regulatory differences, focusing specifically on the role trade agreements might play in addressing regulatory spillovers. A case is made for a greater focus on plurilateral cooperation under the umbrella of the WTO.
Keywords: F13; F23; F53; 330; Nontariff Measures; Regulation; Regulatory Cooperation; WTO; Trade Agreements